Perbandingan Penerapan Good Governance dalam Pemberantasan Korupsi di Indonesia-Filipina - Jasmine, Theresia; Rahmadiani P. N, Arya; Rahma, Aida Aulia; Rahmat, Dadang; Buchori, Rega Imam; Anata, Yudha; Yuningsih, Neneng Yani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this research is to compare Good Government practices between Indonesia and the Philippines using Comparative Government theory. This research uses the literature review method by focusing on literature through books, journals, and published media that are relevant to the issue. The results of this study are seen from 5 indicators of Good Government (The African Development Bank: 1999) which include: Legal and Judicial Reforms, Combating Corruption, Accountability, Transparency, and Participation.